Cotesia flavipes POSSUI CAPACIDADE DE PARASITISMO EM LEPIDÓPTEROSPRAGAS NOCTUIDAE? - DIAS, Pamella Mingotti; LOUREIRO, Elisângela de Souza; PESSOA, Luis Gustavo Amorim; TOSTA, Ricardo Alexandre de Souza; NETO, Francisco Mendes de Oliveira; DEVOZ, Gabriel Luiz Reis (ANAIS DO ENIC, 2018)
-